Wireless Hand Rehabilitation System (WHRS) - (:unkn) unknown (My University, 2017)
0

Loss of motor skills in hand due to several reasons affects daily life in a negative way. Treatment or rehabilitation must be applied in order to reactivate motor skills. Different systems were developed in the rehabilitation process by benefiting telerehabilitation-based or with external skeleton manipulator. An internet connection is required for telerehabilitation-based systems and a physical therapist must carry out the rehabilitation process for systems with external skeleton manipulator. This shall increase the work load of physical therapist. In this study, it is aimed to decrease the work load of physical therapist and develop a hand rehabilitation system with easier and more flexible usage. With this purpose, a system that consists of three units communicate with each other wirelessly and which could be used even without a physical therapist
Keywords: Mühendislik, Elektrik ve Elektronik